Relações de gênero na escola: feminilidade e masculinidade na Educação Infantil - Oriani, Valéria Pall (2013)
The text aims to refl ect about masculinity and femininity in children’s education, an almost entirely feminine environment, bringing fi ndings of a study that investigated the social relations of gender in this level of teaching in a school where a man worked as a teacher. Data was composed by observations of pedagogical practices of a woman teacher and a man teacher of Early Childhood Education. After that, those teachers, the pedagogical coordinator, the headmaster and a nursery worker were interviewed. Based on theoretical contributions about culture and gender, the paper shows that the masculine and the feminine identities and social roles for both sexes, historically, are human constructions that can be modifi ed, especially at school.